A trust-by-design framework for the internet of things - Ferraris, Davide (IEEE, 2018)
The Internet of Things (IoT) is an environment of interconnected entities, that are identifiable, usable and controllable via the Internet. Trust is necessary in a system such as IoT as the entities involved should know the effect of interacting with other entities. Moreover, the entities must also be able to trust a system to reliably use it. An IoT system is composed of different entities from different vendors, each of them with a different purpose and a different lifecycle. So considering trust in the whole IoT system lifecycle is useful and necessary to guarantee a good service for the whole system. The heterogeneity and dynamicity of this field make it difficult to ensure trust in IoT. We propose a trust by design framework for including trust in the development of an IoT entity considering all the phases of the life-cycle. It is composed of the K-Model and transversal activities.
Keywords: Arquitectura de ordenadores; Unified modeling language; Privacy; Security; Internet of Things; Trust; Computer architecture; Adaptation models; Reliability